Garantias legales y constitucionales para los conductores involucrados en accidentes de tránsito con resultados de muerte producidos por la irresponsabilidad del peatón - Lozano Lavayen, Jorge Lorenzo (2016)
This research deals with the lack of legal and constitutional guarantees for drivers involved in traffic accidents resulting in death caused by the irresponsibility of the pedestrian. What we want what we capture with the aim of analyzing the definition in the Code of Criminal Integral wrongful death and enforcement mechanisms guarantees for drivers to accidents caused by irresponsible pedestrian. And we formulate the problem through a guiding question How encouraging that the guarantees normed in the Code of Criminal Integral and the Constitution, for drivers who cause traffic accidents are the result of the irresponsibility of pedestrians are met? The study investigated theme allows hypothesize or idea to defend Reforming the Art 377 of the Code of Criminal Integral, could have a better control mechanism to ensure drivers when a traffic accident caused by a pedestrian happen. Recommend a bill reformatory to Article 377 of the COIP guaranteeing them rights that causes a traff ic accident resulting in death when he avoid hitting a pedestrian or avoid him for disrespecting traffic rules and recommended added to Art is prepared 377 of the Code Integral Penal a clause that says "is exencionara of guilt when the driver is involved in a traffic accident because of the disrespect of the law by the pedestrian or to avoid hitting him him, makes maneuvers that causes death pedestrian or third party liabilities in circulation "…….